Fluid-particle heat transfer in static assemblies: Effect of particle shape. (February 2021) - Chang, Qi; Yang, Liqiu; Ge, Wei
Highlights: An IBM-DNS framework coupling Dirac delta function and ghost cell method is proposed for fluid-particle heat transfer. A specific ghost-cell method for heat transfer from axial-symmetry particles is proposed. Particle shape effect on Nusselt number is described more comprehensively. Correlations are proposed for Nusselt number of prolates and oblates. Abstract: The heat transfer in fluid flow through static assemblies of randomly distributed spheroids, including spheres, prolates, and oblates, is investigated using direct numerical simulation (DNS). Constant heat fluxes are imposed at individual particle surface by the Neumann boundary condition for temperature. The superficial Reynolds number ( Re ) and the solid volume fraction ( φ ) range from 2.5 to 200, and from 0.1 to 0.3, respectively. The simulation results for spheres and prolates agree well with the DNS data and correlations in literature and new correlations for prolates and oblates are proposed. With these results, the particle shape effect on the average Nusselt number ( Nu avg ) is described more comprehensively: At low φ (e.g., 0.1), the Nu avg for prolates and oblates are higher than that of spheres, and as Re increases, the Nu avg of oblates gradually catches up that of prolates and becomes comparable at Re ≈200. Moreover, oblates attenuate and intensify the heat transfer at low and high Re at high φ, respectively.